ECOLOGICAL RISK ASSESSMENT OF HEAVY METALS IN SOILS OF SOME CULTIVATED FLOODED PLAINS IN EKITI STATE, SOUTHWEST NIGERIA - Olayinka D., Akodu; Ademola F., Aiyesanmi; Wasiu B., Tomori; Adebayo E., Adeleke (FUDMA Journal of Sciences, 2025)
A sustainable development goal is adequate supply of safe and quality food; heavy metal contamination of agricultural soil could pose a serious threat to the goal. This study investigates possible heavy metal contamination of some arable cultivated flooded plains by estimating heavy metal levels in soils in order to assess their ecological risks. Soil samples were collected at upper, middle and lower courses of the stream by sampling 0-30cm plough able depth at 5, 25 and 45 m perpendicular to each river. The samples were air-dried, milled, sieved and analyzed for Cd, Cu, Cr, Cd, Zn, Pb and Fe using Atomic Absorption Spectrophotometer (AAS) Perkin Elmer Analyst 400 model. All the metals studied were detected except in few samples. The heavy metal concentration ranges (mg/kg) at Irintan floodplain were: Cr (BDL-0.33), Cu (0.07-0.80), Zn (0.20-2.16), Cd (BDL-0.70), Pb (0.03-0.53), Fe (0.51-2.51). At Omi-Eye floodplain the heavy metal ranges (mg/kg) were: Cr (0.25-2.52), Cu (0.11-8.07), Zn (0.16-3.55), Cd (BDL-0.34), Pb (0.18-0.77) and Fe (0.83-9.05) while at Egbigbu floodplain, the heavy metal ranges (mg/kg) were Cr (0.09-0.79), Cu (0.16-9.70), Zn (0.16-2.27), Cd (BDL-0.12), Pb (0.09-1.02) and Fe (0.72-8.32). The contamination factor, degree of contamination and pollution load index all indicated low pollution status. It is recommended that government should ensure that toxic metals do not build up in our environment through regular monitoring.